Study protocol for a randomised controlled trial investigating two different refeeding formulations to improve safety and efficacy of hospital management of adolescent and young adults admitted with anorexia nervosa. Issue 10 (7th October 2020) - Parker, Elizabeth; Flood, Victoria; Halaki, Mark; Wearne, Christine; Anderson, Gail; Gomes, Linette; Clarke, Simon; Wilson, Frances; Russell, Janice; Frig, Elizabeth; Kohn, Michael
Abstract : Introduction: Providing effective nutritional rehabilitation to patients hospitalised with anorexia nervosa (AN) is challenging, partly due to conservative recommendations that advocate feeding patients at low energy intakes. An 'underfeeding syndrome' can develop when patients are not provided with adequate nutrition during treatment, whereby malnourished patients fail to restore weight in a timely matter, and even lose weight. Of particular concern, the reintroduction of carbohydrate in a starved patient can increase the risk of developing electrolyte, metabolic and organ dysfunction. The proposed trial assesses the efficacy and safety of a lower carbohydrate enteral formula (28% carbohydrate) against a standard enteral formula (54% carbohydrate), in adolescent and young adult patients (aged 15–25 years), hospitalised with AN. Methods and analysis: The study employs a double-blind randomised controlled trial design. At admission to hospital, malnourished adolescent and young adults with AN will be randomly allocated to commence feeding on a standard enteral feeding formula (1.5 kcal/mL, 54% carbohydrate) or a lower carbohydrate isocaloric enteral feeding formula (1.5 kcal/mL, 28% carbohydrate). Assessments of nutritional intake, weight and biochemistry (phosphate, magnesium, potassium) will be conducted at baseline and during the first 3 weeks of hospital admission. The primary outcome measure will be incidence of hypophosphatemia. Secondary outcomes include weight gain, oedema, other electrolyte distortion, length of hospital admission, admission to the Intensive Care Unit (ICU) and number of days to reach medical stability, using defined parameters. Ethics and dissemination: The protocol was approved by the Western Sydney Local Health District Human Research Ethics Committee and institutional research governance approvals were granted. Written informed consent will be sought prior to study enrolment. Study findings will be widely disseminated through peer-reviewed publications and conference presentations. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12617000342314); Pre-results.